2021
DOI: 10.3390/audiolres11030038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial for Cartilage Conduction Hearing Aid in Indonesia

Abstract: Hearing improvement represents one of the may valuable outcomes in microtia and aural atresia reconstruction surgery. Most patients with poor development in their hearing function have had a severe microtia. Conventional methods to improve hearing function are bone conduction and bone anchored hearing aids. Cartilage conduction hearing aids (CCHA) represents a new amplification method. This study assessed the outcomes and evaluated the impact and its safety in the patients with microtia and aural atresia whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…No significant difference in FG was found between purchasers and non-purchasers at any frequency, suggesting that threshold increases in the two groups were similar. Previous reports have also indicated that CC-HAs improved hearing thresholds at all frequencies, regardless of the purchase outcome of CC-HA trials [ 6 , 7 , 17 ]. In summary, this trial of CC-HAs for patients with hearing loss demonstrated a similar functional gain in both non-purchasers and purchasers.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…No significant difference in FG was found between purchasers and non-purchasers at any frequency, suggesting that threshold increases in the two groups were similar. Previous reports have also indicated that CC-HAs improved hearing thresholds at all frequencies, regardless of the purchase outcome of CC-HA trials [ 6 , 7 , 17 ]. In summary, this trial of CC-HAs for patients with hearing loss demonstrated a similar functional gain in both non-purchasers and purchasers.…”
Section: Discussionmentioning
confidence: 93%
“…Certainly, CC-HAs may provide less effective hearing compensation than BC-HAs. However, CC-HAs are small and lightweight, and there is no pain or occurrence of skin laceration due to transducer pressure with a fixation headband, which is common with BC-HAs [ 3 , 4 , 17 , 18 ]. This feature is considered one of the advantages of CC-HAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to BC, the current Special Issue covers the topics of cartilage conduction (CC) and soft tissue conduction [ 6 , 7 , 8 , 9 , 10 , 11 ]. In particular, CC, in which the transducer is placed on the aural cartilage, is highlighted, owing to the benefits and advantages of its devices in atretic ears.…”
mentioning
confidence: 99%
“…CC hearing aids have already been used in clinical practice in Japan since 2017 and have gained popularity, surpassing implantable BC devices in terms of the number of new cases. These new hearing devices will be available in other countries [ 11 ], and several patients will benefit from them in the near future. This Special Issue provides up-to-date information on these novel hearing aids.…”
mentioning
confidence: 99%